Trend, instability and decomposition analysis of coffee production in Ethiopia (1993–2019). Issue 9 (September 2021) - Ayele, Assefa; Worku, Mohammed; Bekele, Yadeta
Abstract: Measuring the trends of growth and variability in agricultural production is important to understand how outputs change over time. Ethiopia is the largest producer of coffee in Africa and the fifth in the world. Despite the abundant opportunities and continuous efforts made to enhance its production, it is often said that the productivity of Ethiopian coffee remains far below its potential. Yet, empirical data on the status of coffee production over time in Ethiopia is scant. We, thus, analyzed the trend, instability, and decomposition of coffee production in Ethiopia for three periods, i.e., the entire period (1993–2019), the pre-Agricultural Growth Program period (1993–2010), and the Agricultural Growth Program period (2011–2019). In all three periods, harvested area and production showed an increasing trend while productivity showed a cyclical decreasing trend. The compound growth rates of harvested area (8.14%) and production (6.68%) in the 1993–2019 period were positive and significant at 1% level, whereas that of productivity (-0.45%) was not significant. Similarly, the compound growth rates of harvested area and production during pre-AGP (6.02 and 6.06%) and AGP (6.43 and 3.57%) were positive, but only significant during AGP, and that of productivity in both pre-AGP and AGP (0.19 and -1.6%) were not significant. Productivity was, however, more stable than harvested area and production during the entire and pre-AGP periods, while harvested area and production were more stable in AGP than in the other two periods. Besides, the harvested area effect on production differentials was substantial in all three periods, while productivity and productivity-harvested area interaction effects declined production during the entire and AGP periods. Overall, the results demonstrate that to enhance and sustain coffee production in Ethiopia, using improved varieties and agronomic practices can be a better option than expanding the cultivation area since land is scarce and fixed in supply. Abstract : Coffee productivity; Compound growth rate; Decomposition analysis; Instability; Production.